THE SHIFT OF ISLAMISM INTO NEOFUNDAMENTALISM AND ITS IMPACT ON ISLAMIC POLITICAL DYNAMICS - Ella Susila Wati; Yuli Imawan; Eri Rahmawati (IAIN Manado, 2023)
Abstract: This article discusses the shift from Islamism to Neo-fundamentalism. Where the term Islamism here is often referred to as Political Islam. Islamism is a movement that makes Islam the basis of its struggle, including organizing the government. Islamism aims to revive Islamic law. But this reemergence of Islamism is not an emergence by Faith but by political claims. Islamism here longs for a historical revival and the glory of Islam, but this endeavor is a fabricated tradition. The emergence of Islamism in Islamic politics is a response to the existence of modernity understood as Western and foreign because it fails to fulfill Islamic interests as understood by Islamism. This failure of Islamism led to a shift towards Neo-fundamentalism towards the end of the 1980s. The neo-fundamentalism movement is very anti-Western. However, militant Islamic groups that previously fought for Islamic revolution shifted to be involved in re-Islamization from below.Key Words: Muslim Brotherhood, Islamism, Olivier Roy, Neofundamentalism